The Effect Of Using A Training Mask On Improving Cardiovascular Adaptation In Athletes - Boumediene , Tarek; Bourenane Cherif, Mustapha; Haceini, Ayoub (sports creativity, 2023)
This study aimed to clarify the importance of using the training mask in developing the efficiency of the cardiovascular system, as it was used as a training tool to improve the efficiency of the heart muscle and strengthen blood circulation during or after physical effort. The experimental method was used on an intended sample consisting of (10) ten Kung Fu Wushu athletes (class of senior males), divided into two groups (control, experimental), and the Ruffier-Dickson test was performed on them using a Smart Pro M4 cardiac watch, where the interval was Between the pre and post measurement (30) thirty days. Through the results of this study, we concluded that the training mask helps in improving the Ruffier-Dickson index as well as improving the resting pulse, which helps in developing the efficiency of the cardiovascular system, and from this we recommend using the training mask in order to develop the capabilities of the cardiovascular system with a strong effect.